The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep35710
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human aldehyde dehydrogenase 1A3 complexed with NAD+ and retinoic acid

Abstract: The aldehyde dehydrogenase family 1 member A3 (ALDH1A3) catalyzes the oxidation of retinal to the pleiotropic factor retinoic acid using NAD+. The level of ALDHs enzymatic activity has been used as a cancer stem cell marker and seems to correlate with tumour aggressiveness. Elevated ALDH1A3 expression in mesenchymal glioma stem cells highlights the potential of this isozyme as a prognosis marker and drug target. Here we report the first crystal structure of human ALDH1A3 complexed with NAD+ and the product all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 47 publications
7
63
0
Order By: Relevance
“…Initial structural studies revealed ALDH7A1 forms a dimerof-dimers tetramer both in crystallo [6][7][8] and in solution [7]. Many other ALDHs form the same tetramer, including ALDH1 [9][10][11][12], ALDH2 [13,14], ALDH5A1 [15], methylmalonate semialdehyde dehydrogenase [16], ALDH21 [17], 2-aminomuconate-6-semialdehyde dehydrogenase [18], betaine aldehyde dehydrogenase [19], lactaldehyde dehydrogenase [20], indole-3-acetaldehyde Abbreviations ALDH, aldehyde dehydrogenase; EM, electron microscopy; PDE, pyridoxine-dependent epilepsy; PLP, pyridoxal-5 0 -phosphate. dehydrogenase [21], a-ketoglutarate-semialdehyde dehydrogenase [22], propionaldehyde dehydrogenase [23], and salicylaldehyde dehydrogenase [24].…”
mentioning
confidence: 99%
“…Initial structural studies revealed ALDH7A1 forms a dimerof-dimers tetramer both in crystallo [6][7][8] and in solution [7]. Many other ALDHs form the same tetramer, including ALDH1 [9][10][11][12], ALDH2 [13,14], ALDH5A1 [15], methylmalonate semialdehyde dehydrogenase [16], ALDH21 [17], 2-aminomuconate-6-semialdehyde dehydrogenase [18], betaine aldehyde dehydrogenase [19], lactaldehyde dehydrogenase [20], indole-3-acetaldehyde Abbreviations ALDH, aldehyde dehydrogenase; EM, electron microscopy; PDE, pyridoxine-dependent epilepsy; PLP, pyridoxal-5 0 -phosphate. dehydrogenase [21], a-ketoglutarate-semialdehyde dehydrogenase [22], propionaldehyde dehydrogenase [23], and salicylaldehyde dehydrogenase [24].…”
mentioning
confidence: 99%
“…a Schematic representation of exons of the ALDH1A3 gene highlighting the positions of all disease causing mutations identified to date. b Domains of predicted protein product as described by Moretti and colleagues [11], highlighting the positions of all disease associated variants identified to date. Discrete color pattern of variants shows type of phenotype (red: anophthalmia, blue: micophthalmia and a combination of red and blue: both anophthalmia and microphthlamia…”
Section: Resultsmentioning
confidence: 99%
“…ALDH1A3 assembles as a tetramer, however, each of its monomeric units is independently able to oxidize retinaldehyde into retinoic acid using NAD as a cofactor. Each monomeric unit folds into 13 α-helices, 19 β-sheets and the connecting loops, arranged into three functional domains: the NAD-binding domains (L20-D149 and I171–G282), the catalytic domain (G283–M482), and the C-terminal oligomerization domains (K150–P170 and S483–L507), [11]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations